2017
DOI: 10.1038/ng.3764
|View full text |Cite
|
Sign up to set email alerts
|

Limited heterogeneity of known driver gene mutations among the metastases of individual patients with pancreatic cancer

Abstract: The extent of heterogeneity of driver gene mutations present in naturally occurring metastases is largely unknown, i.e. treatment-naïve metastatic disease. To address this issue, 60× whole genome sequencing of 26 metastases from 4 patients was carried out. We found that the identical driver gene mutations were present in every metastatic lesion of each patient studied. Passenger gene mutations not known or predicted to have functional consequences accounted for all intratumoral heterogeneity. Even with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
323
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(352 citation statements)
references
References 64 publications
(93 reference statements)
26
323
1
2
Order By: Relevance
“…While the very complex clonal heterogeneity in patients with metastatic disease [72] is under investigation, some studies show that analysis of a single metastasis could be enough to assess major oncogenic driver events because the genomic diversity between metastases is limited [37]. This fact has received confirmation from the evidence in studies on other types of tumors [87]. …”
Section: Genetic/molecular Heterogeneitymentioning
confidence: 67%
“…While the very complex clonal heterogeneity in patients with metastatic disease [72] is under investigation, some studies show that analysis of a single metastasis could be enough to assess major oncogenic driver events because the genomic diversity between metastases is limited [37]. This fact has received confirmation from the evidence in studies on other types of tumors [87]. …”
Section: Genetic/molecular Heterogeneitymentioning
confidence: 67%
“…Probably because of a differential expansion rate, subclones a few centimeters away from each other may be closer genetically than directly adjacent subclones. This could be viewed as a major obstacle when searching for alterations predictive of drug efficacy, yet it has been shown that all of the major tumor driver alterations are present in all subclones [47]. The biological significance of the additional alterations specific to subclones, that represent about 35% of the mutational burden, has yet to be proven to play a role in tumor progression.…”
Section: Primary Tumor Heterogeneitymentioning
confidence: 99%
“…It is involved in differences in the sensitivity of neoplastic cells to targeted therapies. In contrast, in a large scale genomic and genetic analysis, genetic alterations in metastasis sites were found to be maintained as compared to the primary site of tumorigenesis [21]. Thus, this study highlights the interest of a personalized therapeutic combination targeting all the subclonal features of metastases, using proteomics to guide the therapeutic choice.…”
Section: Proteomic Approaches To Search New Biomarkers Of Predictive mentioning
confidence: 81%
“…One or more tumor subpopulations with different characteristics compared to the sensitive cells could emerge allowing them to survive and continue to proliferate in the presence of pharmacological inhibition, leading to a therapeutic failure [19 , 20]. The heterogeneity within tumor is thus a critical component of resistance mechanisms [21]. Technological progress and big data have led to a characterisation of pancreatic cancer's molecular identity (of mostly resected tumors) [22][23][24][25].…”
Section: Targeted Therapies In Pancreatic Cancer -What Can We Learn Fmentioning
confidence: 99%